Impact of capital market performance on foreign portfolio investment in Nigeria - Ogege, S.; Biiranee, K.F.B (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of capital market performance on foreign portfolio investment (FPI) in Nigeria, analyzing key market indicators including the All Share Index (ASI), market capitalization (MCAP), volume of trade (VOT), value of shares traded (VST), and exchange rate (EXR) over the period 1987–2023. Employing an ex post facto research design and time-series data analyzed through econometric techniques such as stationarity testing and regression analysis in EViews, the study reveals significant positive relationships between ASI, MCAP, VOT, and FPI, while VST exhibits a negative association. Exchange rate fluctuations also significantly influence FPI inflows, albeit with lesser strength. The model demonstrates a strong explanatory power with an adjusted R-squared of 0.985, confirming the robustness of the findings. Results support theoretical perspectives including the Efficient Market Hypothesis and Portfolio Theory, highlighting that market size, liquidity, and performance are critical drivers of foreign investment inflows. Policy recommendations emphasize the need to enhance regulatory frameworks, improve market liquidity, strengthen investor education, and maintain exchange rate stability to attract and retain foreign portfolio capital. These measures are vital for deepening Nigeria’s capital market operations and fostering sustainable economic growth.